2015
DOI: 10.1002/jssc.201500549
|View full text |Cite
|
Sign up to set email alerts
|

Natural estrogens in dairy products: Determination of free and conjugated forms by ultra high performance liquid chromatography with tandem mass spectrometry

Abstract: Natural estrogens are synthesized by mammals in different amounts depending on the developmental stage and pregnancy/lactation period, and they may pass into milk, where they are mostly present as glucuronated and sulfated forms. In modern dairy practices, about 75% of milk is produced from pregnant cows; therefore, the amount of hormones that may pass into milk could be of concern. While estrogen determination in milk has been investigated in depth, the individual determination of estrogens and their conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…As it was indicated in the introduction section, only a few studies have been published regarding the evaluation of estrogenic compounds in milk or milk derivatives [6,7,[17][18][19][26][27][28][29] except for kefir samples, which has not been previously analyzed. Concerning cheese samples, it should be indicated that it has only been previously analyzed to determine phyto-, natural and synthetic estrogens, but not mycoestrogens [6,7,17,18]. In this sense, Guoliang et al applied a simple solvent extraction procedure followed by HPLC-FD with a previous derivatization with ethyl-acridinesulfonyl chloride for the determination of E 1, E 2 and E 3 among other type of compounds.…”
Section: Comparison With Other Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As it was indicated in the introduction section, only a few studies have been published regarding the evaluation of estrogenic compounds in milk or milk derivatives [6,7,[17][18][19][26][27][28][29] except for kefir samples, which has not been previously analyzed. Concerning cheese samples, it should be indicated that it has only been previously analyzed to determine phyto-, natural and synthetic estrogens, but not mycoestrogens [6,7,17,18]. In this sense, Guoliang et al applied a simple solvent extraction procedure followed by HPLC-FD with a previous derivatization with ethyl-acridinesulfonyl chloride for the determination of E 1, E 2 and E 3 among other type of compounds.…”
Section: Comparison With Other Methodologiesmentioning
confidence: 99%
“…However, no data related with the sensitivity of the methodology were indicated for this specific matrix. A similar approach was carried out by Chavaliere et al [18] who applied an ultrasound assisted solvent extraction using 1 g of cheese sample and a mixture of 5 mL of MeOH/water (80:20, v/v) containing 1% (v/v) trifluoroacetic acid as extraction solvent, followed by a SPE clean-up step using graphitized carbon black, for the extraction of…”
Section: Comparison With Other Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimation of LOD and LOQ was conducted as already reported . Briefly, a first LOD and LOQ estimation was performed considering the SD of the intercept (σ) and the slope of the calibration graphs ( S ), according to the formulas LOD = 3 σ/S and LOQ = 10 σ/ S .…”
Section: Methodsmentioning
confidence: 99%
“…The most common and reliable analytical techniques for estrogen analysis are separation methods, in particular HPLC [13][14][15][16]. To a lesser extent, MEKC [17,18] and GC [19,20] are also reported.…”
Section: Introductionmentioning
confidence: 99%